The Effect of Regional Government Expenditure on Income Through Economic Output in Jayapura City - Hijrah Irwan; Elsyan R. Marlissa; Agustina Sanggrangbano (LPPM STIE KRAKATAU, 2026)
Purpose: This study examines the effect of regional expenditure on economic output and per capita income in Jayapura City, and tests whether economic output mediates this relationship under fiscal decentralization and Papua's Special Autonomy policy. Methodology: A quantitative approach was applied using annual time series data for 2010 to 2024 from the Central Statistics Agency, the Directorate General of Fiscal Balance, and the regional budget realization of Jayapura City. Data were analyzed using Ordinary Least Squares regression supported by the Augmented Dickey-Fuller test, classical assumption tests, Newey-West robust standard errors, path analysis, and the Sobel test. Results: Regional expenditure positively and significantly affects economic output and per capita income. Among expenditure components, only goods and services expenditure is significant, while personnel and capital expenditure are not. Economic output does not mediate the relationship between regional expenditure and per capita income. Conclusions: Gains in per capita income are driven more directly by regional expenditure than by the transmission mechanism through economic output. Limitations: The study is constrained by a limited number of annual observations, a single expenditure-output-income framework, and a single-city scope. Contributions: The study integrates expenditure composition, economic output, and per capita income within one path model and provides empirical evidence of a growth-welfare disconnect in a fiscally dependent region under Special Autonomy.